(untitled) (Research, Society and Development, 2022)
Currently, it is widely distributed, various information deposited through social networks, increasing on a large scale the amount of influencer profile that bombard tips on how to get thin, bringing advice on food, without having an academic training. This puts the health of the population at risk, as their erroneous and inaccurate instructions directly impact the dietary behavioral patterns of the people who follow them, resulting in changes in the way of eating in which the female audience is the most affected. Women are in search of information about bodies and food, as they are always in a constant attempt to find perfection, bringing with them possible disorders and low self-esteem. This study aimed to investigate the impact that influencers have on women’s eating behavior. Observational, qualitative and descriptive study, a group of 88 women who use social networks and follow Brazilian fitness influencers, answered an online form, disseminated through social networks, carried out and collected in 2022. When analyzed, they showed that the tips and Posted fad diets can have negative impacts on women’s eating behavior, as 44% report feeling guilty when eating, and 74% feel their body is inferior when compared to influencers, and 67% have already changed eating habits. Thus, this study is necessary to challenge information that is not provided by health professionals, such as the nutritionist, and to intensify the importance of priority of individualized care to improve the health of the population.